Topology optimisation of lattice telecommunication tower and performance-based design considering wind and ice loads. (October 2020) - Tsavdaridis, Konstantinos Daniel; Nicolaou, Andreas; Mistry, Anand Dipak; Efthymiou, Evangelos
Highlights: Structural topology optimisation of telecommunication towers. Improved weight-to-stiffness ratio and perceived aesthetic being less visually intrusive. Combination of 2D and 3D approaches with a focus on developing restrained braced systems. Modal analyses of slender optimised tower and a comparative study. Reduced wind drag employing elliptical hollow sections (EHS) for longer members. Abstract: With increasing demand of infrastructure to support power transmission and telecommunication systems, the need of erecting more towers has also been rising significantly. For many years, these towers were designed by using a conservative approach and the opportunities lying in the design optimisation of the towers were not leveraged. This paper presents the application of structural topology optimisation to lattice self-supported telecommunication towers in developing an improved solution in terms of weight-to-stiffness ratio. 2D and 3D topology optimisation studies were performed with highly optimised bracing systems reducing the amount of steel material used, thus its carbon footprint. The new exoskeleton structure is representing a lattice tower composed of 'high-waisted' bracing type and elliptical hollow sections (EHS). Comparative modal analyses demonstrated the structural performance of the optimised tower models. In addition, a research-led design was carried out for optimising the geometric cross-sectional properties of the optimised lattice tower subjected to quasi-static analysis followed by regression analysis. The cross-sectional parameters were progressively changed; explicitly the diameter and thickness of the members. The performance-based analysis and design of a topologically optimised lattice tower present alternatives to onerous approaches such as wind tunnel testing or finite element modelling. The results were further analysed to understand their viability in different loading design cases and the effect of cross-sections. Conclusions highlighted the benefits gained by introducing the structural topology optimisation process in the design of slender support structures.